A Modern "Micro-Ice Age": Implications for Treeline Ecotonal Climate Change Ecology - Kullman, Leif; Öberg, Lisa (European Journal of Applied Sciences, 2025)
In this study we focus primarily on transient ecological responses of the treeline ecotone to a break (~1940s-1980s) admidst the general climate warming of the past 100 years. The study concerns the southern Swedish Scandes and draws on rephotography of individual trees and groups of trees, systematically distributed along permanent elevational transects. The present results comprise a period of general climate cooling and geoecological destabilization, reported from different parts of the northern hemisphere. This course of change culminated during the 1980s, when winter temperatures in northern Sweden were 3-4 °C lower than the mean of the 1930s. For example, permafrost expansion, slow-down of glacier retreat, harvest/reforestation failure and faunal contractions belong to the picture of widespread periglaciation. Characteristic arboreal features in the Scandes and adjacent regions included canopy dieback, defoliation, premature mortality of individual stems, reduced tree regeneration and local minor retreat of the alpine treeline (boreal tree species). These circumstances, following on the relatively warm first decades of the 20th century, sustain the importance of climate forcing for the life and dynamics of the treeline ecotone, which is here proven to respond swiftly (position, structure and species composition) to modest short-term climatic fluctuations. The crucial importance of individual phenotypic flexibility in that respect is clearly manifested by resumed growth of stressed biological systems back to states prevailing prior to and around the onset of the concerned temperature hiatus. Given that current climatic and treeline trends prevail, a major transformation of the subalpine/low alpine landscape may eventually take place, with Pinus sylvestris as the winning part.